Arid Environments and Sustainability - Arman, Hasan; Yuksel, Ibrahim (IntechOpen, 2018)
Arid environments are basically associated with water scarcity. Therefore, soils will have an extremely low moisture level to support plant and animal life as well as human social life. Sustainability is the long durability of systems and processes within various adapted environmental conditions. Recently, systematic scientific studies on arid environments and sustainability have become more attractive, critical, and sound than the previous years. Sharing such experiences related to different environmental circumstances will absolutely help scientists and decision-makers to have better interpretation of their own environment. By learning lessons, appropriate, fast, and effective approaches require to implement for overwhelming such problems. Such actions will certainly lead to more secure and sustainable environments for plant, animal, and human life.